Structural diversity and biological properties of secondary metabolites from sea hare (Aplysia dacdtylomela) and Alcyonacean soft corals - Kishneth Palaniveloo (2015)
North Borneo, located in the Coral Triangle Region (CTR), the world's marine mega biodiversity, has an extremely rich source of marine life. The marine ecosystem is a fusion of complex interaction between the marine environment and marine organisms leading to predatory, competition for space or habitat, protection from disease or infection and directly imposing the pressure to survive among slowmoving, sessile soft bodied marine invertebrates. Thus, marine invertebrates biosynthesize secondary metabolites as a means ,of self defence. Recent development in drug discovery has revealed the potential of marine secondary metabolites as lead pharmaceutical drugs. This research focuses on two invertebrates; the sea hare Aplysia dactylomela Rang and Alcyonacean soft corals (Lobophytum pauciflorum, Sinularia flexibilis and Scleronephthea corymbosa) to investigate the structural diversity of secondary metabolites and its biological potentials. Populations of A. dactylomela from Dinawan Island yielded 10 compounds, Sulug Island yielded 9 compounds and Mantanani Island yielded 12 compounds, comprising of five new compounds with two new chemical skeletons. Compounds were mostly halogenated and comprised of acetogenins, charmigrane, cuparane, syndrean and bromoindoles. Three Alcyonacean soft coral species were analysed to contain 22 secondary metabolites; Lobophytum pauciflorum yielded 6 compounds, Scleronephthya corymbosa yielded 6 compounds and Sinularia flexibilis yielded 10 compounds comprising of furanocembranoids, pregnane type strerols and cembrane diterpenes. Secondary metabolites from the soft corals yielded five new compounds. Structure eluddation of compounds was determined via 10-NMR (proton and carbon), 2D-NMR (HSQC, COSY, HMBC and NOESY), HRMS and FTlR measurements. Sesquiterpenes (+)-elatol (16) and 2,3,5,6-tetrabromoindole (22) inhibited the growth of Escherichia coli (HP0408) and Vibrio cholera (HP0908) at MIC 5 µg/mL and 10 µg/mL. The syndrean 12-acetoxypalisadin B (0.02 %)(13) and pregnane sterol P3N-4 (0.01 %) (32) displayed cytotoxicity towards HL60 (13 µg/mL) and B16FI0 (17 µg/mL) cancer cell line respectively while the furanocembranoid SCl-8 (0.01 %) (28) best suppressed inflammation in LPS induced RAW 264.7 cell and zebra fish embryo at 10 µg/ml concentration. As such, the adaptation of marine invertebrate in the marine environment caters to great potential as an important source of lead pharmaceutical metabolites.